Improving educator development by innovation in teaching activity via web 2.0 - Abdullah, Nurhanim Saadah; Abd Aziz, Mohd Ismail; Ismail, Affero; Hashim, Suhaizal (IOP Publishing, 2017)
Preparing insightful teaching and learning materials for a lesson does need the effort from the educators. Educators should make some research of suitable ways to improve their teaching and learning sessions. In this 21st century, technologies are widely used as tools for education. Even so, there are educators that willing to support and some who do not agree to change. The aim of this study is to develop an innovation teaching materials by applying web 2.0 tools. The intention is to broaden knowledge and in the same time getting response and feedback from people regarding the teaching and learning session materials produced with proper instruction. Action research was used to give a structured flow of this study. The outcome of this study was encouraging and the reflection of this study can help educators in improvising their teaching and learning sessions and materials using action research.